Wireless power transfer framework for minirobot based on resonant inductive coupling and impedance matching - Kin Yun Lum; Jyi-Shyan Chow; Kah Haur Yiauw (International Journal of Power Electronics and Drive Systems (IJPEDS), 2020)
Minirobots which are under the field of miniature robotics, have a dimension of a few centimetres to even a few millimetres. Conventionally, these small sized robots are usually powered up by batteries. The batteries can take up a lot of space and result in a bulky system. Isolating the energy storage components from the robot itself can provide a good alternative to further down sized the robot. This can be done with the incorporation of wireless power transfer (WPT) technology. However, studies of small-size WPT are usually reported with poor efficiency. The objective of this paper is to present an efficient wireless power transfer framework for the minirobot by employing the resonant inductive coupling together with impedance matching technique. The theory and design process will be discussed. Then, a simple prototyping experiment was conducted to verify the proposed framework. Result showed 35% transfer efficiency had been achieved on a transmission distance of 0.5 cm. The proposed framework had also successfully powered a 4 watts minirobot prototype at about 16% transfer efficiency where its receiver coil was located 3.5 cm above the transmitter coil.